An Investigation of Deborah Tannen's Theory of Male and Female Language on Facebook - Cok Agung Anre Juniana (Universitas Pendidikan Ganesha, 2011)
This study focused on investigating the existence of areas of conflicts in a recorded written conversation of young male and female in Facebook. The investigation was based on Deborah Tannen’s theory of the six conflicts between male and female language. The findings show that the six-conflicts exist in written language between male and female. It confirmed that gender is a strong feature in a language that affects people in their ways of communication.